Functional consequences of transferrin receptor‐2 mutations causing hereditary hemochromatosis type 3. Issue 3 (6th March 2015) - Joshi, Ricky; Shvartsman, Maya; Morán, Erica; Lois, Sergi; Aranda, Jessica; Barqué, Anna; de la Cruz, Xavier; Bruguera, Miquel; Vagace, José Manuel; Gervasini, Guillermo; Sanz, Cristina; Sánchez, Mayka
Abstract Hereditary hemochromatosis (HH) type 3 is an autosomal recessive disorder of iron metabolism characterized by excessive iron deposition in the liver and caused by mutations in the transferrin receptor 2 (TFR2) gene. Here, we describe three new HH type 3 Spanish families with four TFR2 mutations (p.Gly792Arg, c.1606‐8A>G, Gln306*, and Gln672*). The missense variation p.Gly792Arg was found in homozygosity in two adult patients of the same family, and in compound heterozygosity in an adult proband that also carries a novel intronic change (c.1606‐8A>G). Two new nonsense TFR2 mutations (Gln306* and Gln672*) were detected in a pediatric case. We examine the functional consequences of two TFR2 variants (p.Gly792Arg and c.1606‐8A>G) using molecular and computational methods. Cellular protein localization studies using immunofluorescence demonstrated that the plasma membrane localization of p.Gly792Arg TFR2 is impaired. Splicing studies in vitro and in vivo reveal that the c.1606‐8A>G mutation leads to the creation of a new acceptor splice site and an aberrant TFR2 mRNA. The reported mutations caused HH type 3 by protein truncation, altering TFR2 membrane localization or by mRNA splicing defect, producing a nonfunctional TFR2 protein and a defective signaling transduction for hepcidin regulation. TFR2 genotyping should be considered in adult but also in pediatric cases with early‐onset of iron overload.